International reserves, current account imbalance and external debt in East Asian economies - Nor, Eliza (2009)
This study investigates the impact of current account imbalance and external debt on international reserve holdings in nine East Asian economies, namely China, Indonesia, Japan, Korea, Malaysia, the Philippines, Singapore, Taiwan, and Thailand (henceforth East Asia). These countries are further divided into four groups: East Asia, ASEAN5, ASEAN4, and the non-ASEAN countries. After the 1997-98 East Asian financial crisis, these countries had increased their reserve holdings and the current accounts in majority of these countries had experienced consistent surpluses at least until 2005. Besides, most of these countries had also increased their external debt holdings in recent years. The autoregressive distributed lag (ARDL) approach, panel cointegration, and panel fully modified ordinary least squares (FMOLS) were utilized to examine the relationship between international reserve holdings and its determinants. The study covers the period from 1970 to 2005. There are three important conclusions can be derived from the empirical findings. First, current account balance has a positive and significant relationship with international reserve holdings in Indonesia, Japan, Korea, Malaysia, Singapore, Taiwan, East Asia, ASEAN5, ASEAN4, and non-ASEAN countries. The positive relationship indicates that the rise in the current account surplus leads to the rise in international reserve holdings in these countries. Second, total external debt is a substitute for international reserves in China, Japan, Korea, the Philippines, East Asia, ASEAN5, and ASEAN4. Third, short term external debt acts as a substitute for international reserves in Korea, the Philippines, Thailand, ASEAN5, and ASEAN4. The role of external debt as substitute for international reserves implies that external debt is used to finance international transactions. However, in China, Singapore, and the non-ASEAN countries, short term external debt acts as a complement for international reserves. In other words, these countries increased reserves as their precautionary measure against short term capital flow reversals during the crisis. High international reserve holdings and current account surplus are associated with the savings investment imbalance in East Asia. The imbalance is due to the limited ability of the private sector to transform its savings into investment. The development in the regional capital markets may assist the private sector to circulate its savings within the region and minimize its dependence on external financing.